Free-hand technique of C7 pedicle screw insertion using a simply defined entry point without fluoroscopic guidance for cervical spondylotic myelopathy patients with C3 to C6 instrumented by lateral mass screws: a retrospective cohort study - Jun Jiang; Chen-yu Song; Zheng-zheng Wu; Zuo-zhi Xie; Bo Shi; Tao Xu; Han Wang; Yong Qiu; Bin Wang; Ze-zhang Zhu; Yang Yu (BMC Surgery, 2024)
Abstract Background Nowadays, both lateral mass screw (LMS) and pedicle screw were effective instrumentation for posterior stabilization of cervical spine. This study aims to evaluate the feasibility of a new free-hand technique of C7 pedicle screw insertion without fluoroscopic guidance for cervical spondylotic myelopathy (CSM) patients with C3 to C6 instrumented by lateral mass screws. Methods A total of 53 CSM patients underwent lateral mass screws instrumentation at C3 to C6 levels and pedicle screw instrumentation at C7 level were included. The preoperative 3-dimenional computed tomography (CT) reconstruction images of cervical spine were used to determine 2 different C7 pedicle screw trajectories. Trajectory A passed through the axis of the C7 pedicle while trajectory B selected the midpoint of the base of C7 superior facet as the entry point. All these 53 patients had the C7 pedicle screw inserted through trajectory B by free-hand without fluoroscopic guidance and the postoperative CT images were obtained to evaluate the accuracy of C7 pedicle screw insertion. Results Trajectory B had smaller transverse angle, smaller screw length, and smaller screw width but both similar sagittal angle and similar pedicle height when compared with trajectory A. A total of 106 pedicle screws were inserted at C7 through trajectory B and only 8 screws were displaced with the accuracy of screw placement as high as 92.5%. Conclusion In CSM patients with C3 to C6 instrumented by LMS, using trajectory B for C7 pedicle screw insertion is easy to both identify the entry point and facilitate the rod insertion.